Student Perceptions Of AI-Based Decision Support Systems: A Descriptive Statistical Analysis - Afrigh Elena Shabra; Tika Endah Lestari (Jurnal Ilmiah Teknik Informatika (TEKINFO), 2026)
The rapid development of artificial intelligence (AI) has influenced many aspects of students’ academicactivities, especially in decision-making processes. Many university students now use AI-based tools to helpthem understand assignments, generate ideas, and evaluate information during their studies. This study aimsto examine students’ reliance on AI-based decision support systems and identify several related factors,including trust and critical thinking. A quantitative survey method was used in this research, and data werecollected from 60 university students from different academic backgrounds in the Jabodetabek area throughan online questionnaire distributed using Google Forms. The collected data were analyzed using descriptivestatistics. The findings showed that AI tools were widely used among students, with many respondentsdemonstrating moderate to high levels of reliance on AI systems. Although students tended to trust AIgeneratedoutputs, many respondents still evaluated the information critically before using it in academictasks. However, some respondents also believed that excessive AI usage could reduce independent thinkingabilities. Overall, the findings suggest that AI provides both benefits and potential risks in academic contexts.Therefore, students should use AI in a balanced and critical manner so that technology can support learningwithout reducing independent thinking and decision-making abilities.